Heteroaromatic benzyl ethers as intermediates for palladium-catalysed transfer hydrogenolysis of benzyl alcohols - Araujo, Nuna C. P. (2014)
A chemoselective and easy to carry procedure for the hydrogenolysis of benzyl alcohols is described. Benzyl alcohols are readily converted into tetrazolyl and benzisothiazolyl ethers that can be catalytically hydrogenolysed to toluenes over palladium-on-charcoal using hydrogen donors. The effect of electronwithdrawing heteroaromatic substituents is interpreted on the basis of chrystallographic structure determinations and molecular orbital calculations.